Achieving Simplicity with the Three-Layer Product Model. - Bosch, Jan (Computer (00189162), 2013)
Increased system complexity has historically been treated as an inevitable consequence of architecture evolution over time. The three-layer product model offers an innovative framework for managing system growth that encourages greater efficiency, nimbler responsiveness, and more opportunities for innovation during all stages of the software development life cycle.